A dye encapsulated zinc-based metal–organic framework as a dual-emission sensor for highly sensitive detection of antibiotics. Issue 2 (15th December 2021) - Wang, Kang; Duan, Yuhan; Chen, Jiajing; Wang, Haiying; Liu, Huiyan
Abstract : Incorporated amide groups enable the tetratopic linker to facilitate diversity nets of lon (1 ) and nbo (2 ). Importantly, fluorescent dye DMASM can be encapsulated into 2 as a dual-emitting sensor for highly sensitive detection of antibiotics. Abstract : Self-assembly of two Zn-MOFs, [Zn2 L(DMF)3 ] · H2 O·5DMF (1 ) and [Zn2 L(H2 O)2 ] · 4H2 O·3DMF (2 ), was achieved with an amide-functionalized tetracarboxylate ligand under similar conditions. Incorporated amide groups make the tetratopic linkers exhibit different configurations, tetrahedron and square, and subsequently combine tetrahedral [Zn2 (CO2 )4 ] clusters or square paddle-well [Zn2 (CO2 )4 ] clusters to afford a lon net for 1 and a nbo net for 2 . Remarkably, 2 demonstrated high porosity and amide group decorated cages, and thereby proved to be a good capturing agent for a fluorescent dye molecule (DMASM). Consequently, a dual-emitting DMASM@2 sensor was successfully fabricated based on effective energy transfer from the host framework to DMASM with the variable luminescent color being visible to the naked eye. DMASM@2 could be used for the detection of metronidazole (MDZ) and dimetridazole (DTZ) with high sensitivity and remarkable recyclability.